2022
DOI: 10.7759/cureus.26382
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Hypothyroidism With Disease Activity Score-28 in Patients of Rheumatoid Arthritis

Abstract: IntroductionRheumatoid arthritis (RA) is a chronic autoimmune disorder with variable disease course including periods of flares and remissions. High disease activity in terms of disease activity score-28 (DAS-28) results in significant morbidity. Hypothyroidism is found to be associated with higher DAS-28 scores in RA. This study is planned to determine overt and subclinical hypothyroidism and its correlation with the DAS-28 score in patients with RA. MethodologyThis study was conducted from June 2021 to March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…( 11 ). Previous studies have indicated that RA coexisting with hypothyroidism may increase disease activity and joint tenderness ( 33 ). Three large-scale GWAS summary datasets were chosen to ensure robust heritability interpretation for hypothyroidism and RA.…”
Section: Discussionmentioning
confidence: 99%
“…( 11 ). Previous studies have indicated that RA coexisting with hypothyroidism may increase disease activity and joint tenderness ( 33 ). Three large-scale GWAS summary datasets were chosen to ensure robust heritability interpretation for hypothyroidism and RA.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies have shown a correlation between the disease activity score -28 (DAS-28) and hypothyroidism in RA patients. Hypothyroidism may increase disease activity due to an increase in joint pain, so RA patients should be aware of thyroid function screening for early detection and better treatment ( 32 ). One of the most prevalent co-morbidities of RA is hypothyroidism; however, the shared pathophysiology between the two conditions is still unknown, and genes implicated in the control of T cell responses may be important ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…They found that post-thyroidectomy TPOAb levels decreased from a mean of 339 to 59 IU/L, and there were major improvements in patients’ associated autoimmune features including RA [ 61 ]. These common and overlapping immune activation pathways may help to explain the reported exacerbation of disease activity in patients with an RA and AITD overlap [ 62 , 63 ].…”
Section: Effect Of Aitd On Ra Disease Activitymentioning
confidence: 99%